DEPRECIATION AND AMORTIZATION OF FIXED ASSETS IN FISCAL INSTITUTIONS AND COMMERCIAL ENTERPRISES - Trush, Yu. T.; Korol, H. O.; Kucynska, M. V. (Science and Transport Progress, 2010)
The comparison of methods of extra charge of wear of the fixed assets in budgetary establishments and their amortization in business enterprises is conducted. The procedure of choice of amortization method for an object of the fixed assets in business enterprises is grounded.